Peranan Organisasi dalam Meningkatkan Koordinasi Kerja pada Satuan Direktorat Lalu Lintas Polda Jabar - Mai Marini; Quratal Aeni; Ilham Agustian Widia Yusuf; Ahmad Farihin (Al-Qiyadi Jurnal Manajmen Pendidikan Islam, 2023)
This study aims to analyze the construction, operationalization, and development design of Electronic Traffic Law Enforcement (ETLE). The research approach is a qualitative method with data collection techniques and interviews. The research instrument is an interview guide. Informants include personnel: the National Police, transportation services, and banks. Some of the obstacles in the current implementation of ETLE include: Limited availability and capacity of ETLE cameras, disintegration of recording data, data inconnectivity, variations in the availability of budgets for each Regional Police for procuring cameras used in ETLE operations, out of sync in regulatory provisions regarding manual ticketing, and electronic ticketing.